Cost Performance Evaluation of The Improvement of The Wirosari-Karangasem Road Section, Wirosari District Uses Method (Earned Value Concept) - Irawan, Arie Kris; Suwandi, Putri Anggi Permata; Kristiawan, Agung (Science and Technology Research Centre, Universitas PGRI Semarang, 2024)
In construction projects that occur in Indonesia, implementation often experiences delays and cost losses where the realization in the field does not match the planned schedule and planned budget due to several factors that occur, even though a thorough cost plan has been prepared, in practice in the field there are still many problems that arise problems in implementation. So the Earned Value Concept or EVM (Earned Value Method) method is used to overcome this problem to determine the implementation cost performance during the project and the indicators used for analysis include: BCWP (Budget Cost of Work Performance), BCWS (Budget Cost of Work Schedule), ACWP (Actual Cost of Work Performance), SV (Schedule Variance), CV (Cost Variance), SPI (Schedule Performance Index), CPI (Cost Performance Index), ETS (Estimated Temporary Schedule), and EAS (Estimated All Schedule). This research aims to evaluate the cost performance of the Wirosari - Karangasem Subdistrict road section improvement project. Wirosari uses the Earned Value Concept method. This method is used to measure project performance by comparing the value of the results achieved (Earned Value) with the planned value (Planned Value) and target value (Budgeted Cost of Work Performed) from week 1 to week 16 using the Concept Earned Value or EVM (Earned Value Method). From the results of this research, the performance of project implementation costs or calculations is knownCost Performance Index (CPI) Whichcut offweek 16 of 34 weeks in the period 6 to 12 May 2024 was 1.156 and there was no CPI value 1 with Cost Variation (CV) week 16 amounting to IDR 589,440,708.64, so that if the project implementation performance in the weekly reporting remains the same until the project is completed, the estimated costs required to complete the remaining project work orEstimate To Complete (ETC) amounting to IDR 1,294,766,228.89 so that the total estimated project costs required to complete the project work orEstimate At Completion (EAC) is IDR 5,075,881,759.65 and the estimated profit obtained from the project or Variance At Completion (VAC) is IDR 791,424,240.35